Synthesis of acetylcholine receptor during differentiation of cultured embryonic muscle cells. - Merlie, J P (1975)
Acetylcholine receptor, a component of the specialized muscle membrane, appears during the differentiation of embryonic myogenic cells in tissue culture. Demonstration of incorporation of the radioactive precursor L-[35S]methionine into purified receptor polypeptides is presented as evidence for its synthesis de novo. The identity of the purified radioactive species is established by cosedimentation of the [35S]receptor with [3H]alpha-toxin binding activity on sucrose gradients and by crossreaction with antiserum to purified acetylcholine receptor of Electrophorus electricus.